Frequency of PPHN in Neonates Having Confirmed Diagnosis of Meconium Aspiration Syndrome - Sumbal Abbas, Madiha Jameel, Nagham Nawaz Awan, Sumera Abdul Karim, Maha Anwar (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Optimal oxygenation, avoidance of respiratory and metabolic acidosis, normal blood pressure, sedation & pulmonary vasodilator treatment are among the management techniques for persistent pulmonary1hypertension of the newborn. Aim: To find frequency of PPHN in neonates having confirmed diagnosis of meconium aspiration syndrome. Study Design: Descriptive cross sectional study. Methodology: Total 240 neonates who fulfilled inclusion criteria were enrolled from Pediatrics Medicine Ittifaq hospital Lahore after getting informed consent form parents or attendants. Basic information like gestational age, gender, birth weight, APGAR score at 7 minutes, mode of delivery were taken (on antenatal record). All cases with confirmed diagnosis of MAS were underwent 2D Echocardiography and PPHN were diagnosed as per operational definition. All diagnostic procedure was done by a single consultant cardiologists. SPSS 20.0 was utilized to analyze the data. For quantitative data, mean and standard deviation were provided, while frequencies and percentages were provided for qualitative factors. Post stratification Chi-square test was applied taking p-value ≤ 0.05 as significant. Results: The mean birth weight was 3211.02±412.10 grams with min & max birth weight as 2500 and 3882 g. The mean APGAR score was 7.95±1.41. There were 85(35.4%) cases who had PPHN while 155(64.6%) cases did not have positive diagnosis of PPHN. Conclusions: It was concluded that frequency of PPHN in neonates having confirmed diagnosis of meconium aspiration syndrome is very high. So early screening during antenatal visits and adopting preventive strategies can only minimize the risk of meconium aspiration syndrome thus preventing PPHN. Keywords: Persistent Pulmonary Hypertension, Meconium Aspiration Syndrome, Meconium Stained Amniotic Fluid